COLLABORATIVE GOVERNANCE: THE REPRESENTATIVE FUNCTION OF THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) IN POVERTY ALLEVIATION IN TASIKMALAYA REGENCY - Cepi Triana Sapari; Thomas Bustomi; Kamal Alamsyah (RADJA PUBLIKA, 2026)
This study examines the representative functions of the Regional House of Representatives (DPRD) in poverty alleviation through a collaborative governance approach in Tasikmalaya Regency. The research is motivated by the persistence of formalistic representation practices that have not thoroughly reflected the substantive interests of impoverished communities. Within the framework of decentralized and collaborative governance, the DPRD is expected not only to perform its legislative, budgeting, and oversight functions procedurally, but also to actively facilitate cross-actor collaboration in public policy processes. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and document analysis involving DPRD members, local government officials, and civil society actors. The findings indicate that the representative function of the DPRD in poverty alleviation has not been optimally implemented due to institutional constraints, internal political dynamics, and weak collaborative mechanisms with non-government actors. Collaborative governance remains largely normative and has yet to be fully institutionalized in poverty alleviation policies. These findings underscore the importance of strengthening the DPRD's representative function through a more inclusive and substantive collaborative governance model to enhance local poverty alleviation efforts.